The Burden of Hormonal Disorders: A Worldwide Overview With a Particular Look in Italy - Crafa, Andrea; Calogero, Aldo E.; Cannarella, Rossella; Mongioi’, Laura M.; Condorelli, Rosita A.; Greco, Emanuela A.; Aversa, Antonio; La Vignera, Sandro (Frontiers in Endocrinology, 2021)
Endocrine diseases have a considerable impact on public health from an epidemiological point of view and because they may cause long-term disability, alteration of the quality-of-life of the affected patients, and are the fifth leading cause of death. In this extensive review of the literature, we have evaluated the prevalence of the different disorders of endocrinologic interest in the world and Italy, highlighting their epidemiological, clinical, and economic impact.